Classification of Rice Growth Phases with an Object-Based Approach using Sentinel-2 Imagery - Ardiansyah, Muhammad; Munibah, Khursatul; Saniinah, Siti Nur (Jurnal Ilmu Tanah dan Lingkungan, 2023)
Monitoring of rice crops in Indonesia is supported by the local government at the sub-district level. This practice requires a lot of funds and is considered less efficient. Another option is to utilize remote sensing data using Sentinel-2 free satellite imagery to monitor rice growth spatio-temporally and over a wider area. Sentinel-2 is designed to support agricultural monitoring. To monitor the growth phase of rice can be done with a pixel-based classification, but this approach has limitations due to the appearance of salt and pepper that affect the classification results and accuracy. The object-based image analysis approach can overcome this phenomenon and better mimic human perception of objects. This study aims to identify the growth phases of rice in Sentinel-2 imagery using an object-based classification approach, and to monitor the spatio-temporal distribution of rice growth phases. Sentinel-2 imagery with 10 acquisitions in May – August 2021 was analyzed using an object-based approach and the growth phases of rice were classified using the SVM approach. The results show that the growth phase of rice can be identified and classified properly without the salt and pepper phenomenon with an object-based approach from Sentinel-2 multi-temporal imagery. The accuracy of the SVM classification model is good with an average accuracy of 81.60. The object-based SVM classification can map the distribution of rice growth phases consistently and continuously from Sentinel-2 multi-temporal images.